Impact of psychological capital on occupational burnout and performance of faculty members. Issue 4 (8th May 2017) - Rehman, Saif ur; Qingren, Cao; Latif, Yasir; Iqbal, Pervaiz
Abstract : Purpose: The purpose of this paper is to examine the impact and interrelation between positive psychological capital and occupational burnout among faculty associates of technical and professional training institutions. Design/methodology/approach: In total, 282 faculty members from 17 technical institutions were selected from the province of Punjab, Pakistan. Results were drawn using bivariate correlation and linear regression on the data that were collected through adopted questionnaire. Findings: Results of the study revealed that occupational burnout is significantly related to the performance of the faculty of technical institutes and that psychological capital moderates this relationship. Practical implications: Conclusions from this research suggested that the personality trait of a psychological capital is an essential determinant of job burnout and performance among faculty members; therefore, it must be considered as an essential part of the selection criteria and job-assessment process. This is important, since psychological capital reduces the detrimental impact of occupational burnout on performance outcomes. Further the faculty members with higher psychological capital should be retained to create positive work environment which can be an inspiration for others. Originality/value: The research provides important information about the impact of personality traits upon the performance of a faculty member who joins an educational institution coming from an industrial environment. Although having similar technological skills required for the position, still the effects of a new environment can cause performance issues, the research insisted that positive personality traits like psychological capital can help in gaining required confidence to perform in a changed environment.